2018
DOI: 10.1016/j.contraception.2018.08.002
|View full text |Cite
|
Sign up to set email alerts
|

An observational study to test the acceptability and feasibility of using medical and nursing students to instruct clients in DMPA-SC self-injection at the community level in Kinshasa

Abstract: ObjectivesGiven the promise of DMPA-SC to increase community-level access to modern contraception in developing countries, we conducted an observational study to assess the acceptability and feasibility of DMPA-SC self-injection among women in Kinshasa, Democratic Republic of the Congo, and of medical/nursing (M/N) students as instructors for self-injection.Study designWomen who selected DMPA-SC at a community outreach event adjacent to a health center were interviewed upon acceptance (baseline) and then 3, 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 18 publications
(20 reference statements)
3
36
0
Order By: Relevance
“…The findings of this paper also showed that using M/N students as community-based providers was entirely acceptable to FP users in Kinshasa, who generally gave positive evaluations of the services they received. This is consistent with findings from piloting of communitybased provision of DMPA-SC [10,23] in Kinshasa, and similar studies indicating that community-health workers could successfully be used to increase access to contraceptives throughout Sub-Saharan Africa [1,2].…”
Section: Discussionsupporting
confidence: 89%
“…The findings of this paper also showed that using M/N students as community-based providers was entirely acceptable to FP users in Kinshasa, who generally gave positive evaluations of the services they received. This is consistent with findings from piloting of communitybased provision of DMPA-SC [10,23] in Kinshasa, and similar studies indicating that community-health workers could successfully be used to increase access to contraceptives throughout Sub-Saharan Africa [1,2].…”
Section: Discussionsupporting
confidence: 89%
“…Our findings are similar to and contribute to the growing literature about DMPA-SC disposal [38]. Limited published literature exists related to storage and disposal of DMPA-SC, and almost all has been in the context of self-injection offered within research contexts, including Malawi [19,22], Senegal [39], Uganda [30], and the Democratic Republic of the Congo [40]. This is the first study to report on the waste management experiences of adolescent and covert self-injectors within the context of program scale up-important populations expected to especially benefit from self-injection.…”
Section: Strengthssupporting
confidence: 86%
“…Recent studies have shown that CHWs can safely and acceptably administer DMPA-SC in communities 8 10 . Studies have also shown that women can be trained to self-inject, where the practice is permitted and the product is registered as a self-injectable, which allows greater contraceptive control over their fertility 11 , 12 …”
Section: Project Descriptionmentioning
confidence: 99%